Non-Standard Employment in the BRICS Countries - E. Sychenko; M. Laruccia; D. Cusciano; I. Chikireva; J. Wang; P. Smit (BRICS Law Journal)
Non-standardization of employment has become the main trend of the labour markets in the globalized economy. Attempting to enhance the flexibility of employment relations the legislators in BRICS countries are also the part of this trend. The forms of the nonstandard employment are numerous, the present paper concentrates upon the following ones: temporary employment, part-time and multi-party employment relationship. The authors review the experience of four BRICS countries in regulating non-standard forms of employment and determine what were the specific reasons for adopting them in Russia, China, Brazil, and South Africa. The national parts are introduced by the consideration of the international standards of protection of employees working under non-standard contracts. It is argued that even though these four states did not ratify the ILO Convention No. 181 Private Employment Agencies Convention (1997) and only Russia ratified ILO Part-Time Work Convention (No. 175), the ILO approach has influenced the development of national regulations. Though the equal treatment of all workers is lacking in many aspects of employment relations. In the national parts the authors trace the changes in employment law which reflect the pursuit of flexibilization of the labour market and, as in Brazil, the need to formalize employment relations.